( 2х + 3 ) ( х - 4 ) < х^2 + 4х - 12
2х^2 - 8х + 3х - 12 < х^2 + 4х - 12
2х^2 - 8х + 3х - х^2 - 4х < -12 + 12
х^2 - 9х < 0
х ( х - 9 ) < 0.
0 < х < 9.
Удачи)))
1) вынесем общий множитель за скобки:
3 3/8 * 3 1/5 + 3 1/5 * 1 5/12 - 4 1/6 * 3 1/5 = 3 1/5*(3 3/8 + 1 5/12 - 4 1/6)
2) преобразуем то, что получилось в скобке:
3 3/8 + 1 5/12 - 4 1/6 = 27/8 + 17/12 - 25/6 = 81/24 + 34/24 - 100/2 = 15/24 = 5/8
3) выполним последнее действие:
3 1/5 * 5/8 = 9/5 * 5/8 = 9/8
2y+6=21-3y
5y=15
y=3
Ответ: 3
801
х
401
--------------
801
3204
--------------
321201
<em>183</em>34<em>0 </em>|<u> 89
</u><u>-178</u> | 2<em>0</em>6<em>0</em>
<em>5</em>34 |
<u>-534</u> |<u>
</u> 0